2011
DOI: 10.4061/2011/621074
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Blood Pressure Indices among the Residents of a Rural Community in South East Nigeria

Abstract: Cardiovascular diseases (CVDs) are the main causes of death in industrialized countries, and are significant causes of morbidity and mortality in sub-Saharan Africa. Hypertension is the most common cardiovascular disease in Nigerians, and the risk of CVD associated with hypertension is independent of other risk factors. Despite the high level of awareness of its presence in the developed countries, the level of control is still poor. CVDs tend to be commoner in urban settlements, and it has been hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 22 publications
10
47
6
Order By: Relevance
“…However, compared with findings [21,22,[32][33][34][35] in non-Nigerian groups, particularly African-Americans and whites, the present association between BP and body size indicators appears weak. Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study. This weak or lack of a relationship between body dimensions and BP has also been observed in other groups particularly within Africa [7,9,[29][30][31][36][37][38].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…However, compared with findings [21,22,[32][33][34][35] in non-Nigerian groups, particularly African-Americans and whites, the present association between BP and body size indicators appears weak. Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study. This weak or lack of a relationship between body dimensions and BP has also been observed in other groups particularly within Africa [7,9,[29][30][31][36][37][38].…”
Section: Discussioncontrasting
confidence: 80%
“…Also, the differences in measurements of body size between the group with elevated BP and those with normal BP were moderately large, except for WC/HPC (Table 1). This is consistent with many previous reports [29][30][31]. However, compared with findings [21,22,[32][33][34][35] in non-Nigerian groups, particularly African-Americans and whites, the present association between BP and body size indicators appears weak.…”
Section: Discussioncontrasting
confidence: 56%
“…Figure 1 is a summary of the selection process. These cross-sectional studies were published between 1960 and 2012 in 12 of the 36 states of Nigeria: Oyo [9][10][11][12][13][14][15][16][17][18][19][20][21][22] , Enugu [23][24][25][26][27] , Lagos [28,29] , Osun [30,31] , Edo [32][33][34][35] , Cross-River [36,37] , Akwa-Ibom [37] , Rivers [38] , Kastina [39] , Sokoto [40] , Borno [41] and Abia [42] . Three of the studies involved more than one state [37,43] .…”
Section: Resultsmentioning
confidence: 99%
“…Other recent studies also demonstrate an increasing pattern in the prevalence of hypertension ranging from 20.8% [17] , to 23.6% [18] , to as much as 44.5% [19] and 46.4% [6] .…”
Section: Discussionmentioning
confidence: 97%
“…The Nigerian National Non-Communicable Disease Survey in 1997, using a blood pressure cutoff value of 160/95mmHg for hypertension had a prevalence of 11.4% (which could have been higher if the new cutoff value of 140/90mmHg was used) [20] . Other recent studies had reported its high prevalence in the country also [6,18,24] Hypertension constitutes 25% of emergency medical admissions in Urban hospitals in Nigeria [25] and is usually unaccompanied by any signs in its early stages. As a result of these identified changes in epidemiologic trend of hypertension and its complications, there is need to regularly conduct a survey on its prevalence, an important tool for assessing its magnitude, in order to implement effective control strategies (as its awareness, detection, treatment and control has been extremely low due to scarce resources & inadequate health provision) to slow the rise in the disease occurrence.…”
Section: Introductionmentioning
confidence: 99%